PERFORMANCE CRITERIA ABOUT QUALITY MANAGEMENT INTEGRATED CIRCUITS AT THE PRODUCTION - Tomashevskiy, O. V.; Pogosov, V. V. (Radio Electronics, Computer Science, Control, 2008)
On the stage of production quality of integred microcircuits is in a great deal determined stability of technological processes. For research of efficiency of finding out discords of technological processes it is suggested to use the theory of the casual roaming of brownian particle. Integral equalizations of Fredgol of 2th family are got for the estimation of middle lengths of series of selections of the put right or deranged processes and probability of the first output of trajectories for a low bound.